Comprehensive analysis of the ionospheric response to the largest geomagnetic storms from solar cycle 24 over Europe - Berényi, K. A.; Heilig, B.; Urbář, J.; Kouba, D.; Kis, Á.; Barta, V. (Frontiers in Astronomy and Space Sciences, 2023)
A multi-instrumental analysis of the meridional ionospheric response is presented over Europe during the two largest ICME-driven geomagnetic storms of solar cycle #24 maximum. Data from 5 European digisonde stations, ground-based Global Navigation Satellite System, Total Electron Content (GNSS TEC), the ratio of the TEC difference (rTEC), as well as Swarm and Thermosphere, Ionosphere, Mesosphere, Energetics and Dynamics (TIMED) satellite observations have been used for the investigation of selected intervals (11–17 November, 2012, and 16–25 March, 2015). The storm evolution is monitored by digisonde foF2 critical frequency (related to the maximum electron density of F2-layer) and GNSS TEC data. Moreover, Global Ultraviolet Imager (GUVI) measurements from the TIMED satellite are used to investigate the changes in the thermospheric O/N2 ratio. Our main focus was on the main phase of the geomagnetic storms, when during the nighttime hours extremely depleted plasma was detected. The extreme depletion is observed in foF2, TEC and rTEC, which is found to be directly connected to the equatorward motion of the midlatitude ionospheric trough (MIT) on the nightside. We demonstrate a method (beside the existing ones) which allows the monitoring of the storm-time evolution of the disturbances (e.g., MIT, SAPS, SED) in the thermosphere-ionosphere-plasmasphere system by the combined analysis of the worldwide digisonde system data (with the drift measurements and the ionospheric layer parameters with 5–15 min cadence), with rTEC and GNSS TEC data, and with the satellite data like Swarm, TIMED/GUVI.